Analisis penerapan Kesehatan dan Keselamatan Kerja (K3) dalam proyek pembangunan Gedung RSIA Norfa Husada - Adeswastoto, Hanantatur; Sari, Resy Kumala; Saputra, M Azlan; Tasya, Tasya; Nisa, Khoirun; Rahman, Anang Maulana Ar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Norfa Husada Hospital is a multi-storey building construction project that has K3 risks during construction. Therefore, to reduce the number of work accidents that occur during the Norfa Husada-Bangkinang Hospital Building construction project, efforts are needed to identify potential risks of work accidents from each job. This research studies various factors that influence occupational safety and health, how to implement occupational safety and health, and occupational safety and health risks. The aim of this research is to determine the types of risks, the factors that influence them, and how to manage occupational safety and health risks in the Norfa Husada Bangkinang hospital building construction project. The data collection method used in this research was a questionnaire and interview method with 20 respondents consisting of Owners, Contractors, Supervisors. The results of this research obtained a score of 3.3% for workers' comfort and light sources while working, a score of 2.75% because the machine was located far from the project environment, causing injuries or noise, a score of 3.25% for the company that provided a comfortable place to rest, a score of 2.80% for a spacious workplace so that it did not cause clashes with other workers, and a score of 3.30% for the presence of personal protective equipment (PPE) provided on the project.